Choosing the best urban tunnels as safe space in crisis using AHP method: a case study in Iran - Nakhaei, Jalal; Bitarafan, Mahdi; Arefi, Shahin Lale (Journal of Architecture and Urbanism, 2015)
In recent decades, experiences resulted from Modern wars have shown that aggressive armies have targeted vital and sensitive resources of the other countries in order to decrease their expenses in one hand and increase damages in other hand, defending countries transmit their critical and sensitive facilities to safe underground spaces in order to reduce damages, and experience has shown that underground spaces receive the least damage. This study tries to examine and prioritize Tehran tunnels as undergroundsafe spaces at crisis times regarding their structural parameters and also civil defense arrangements. It could accelerate the selection and creation of underground-safe spaces at crisis and it also can decrease construction and maintenance costs. This study has used AHP method to evaluate Tehran tunnels. In this regard five indices have been chosen by asking experts in the related fields and to evaluate and select a proper way to choose the best one as an urban-safe space. Finally, the investigated tunnels are prioritized as Tohid weighted as 0.349, Niyayesh weighted as 0.279, Resalat weighted as 0.197 and finally Amir Kabir weighted as 0.164 respectively that showed Tohid tunnel is the best urban-safe space and, Niyayesh, Resalat and Amir Kabir tunnels take the next places in the ranking, respectively.